Pisonia Alba Assisted Synthesis of Nanosilver for Wound Healing Activity - Suba Kannaiyan; D. Easwaramoorthi; Karthik Kannan; Andal Gopal; R. Lakshmipathy; Khadijah Mohammedsaleh Katubi; Nayef S. Almuaikel; Ivan Leandro Rodriguez Rico (Bioinorganic Chemistry and Applications)
Wound infection is a major clinical challenge, impacting patient morbidity and mortality, with significant economic implications. Our research focused on how Pisonia Alba (PA) leaves, which are used to treat wounds, are used to synthesize silver nanoparticles and study their wound healing property. UV-visible spectroscopy, X-ray diffraction analysis, and s electron microscope (SEM) analysis were employed to evaluate the synthesized silver nanoparticles. Using DLS and Zeta potential analysis, the size and stability of the Pisonia Alba capped silver nanoparticle were investigated. The results showed that Pisonia Alba extract stabilized silver nanoparticles are 63.88 nm in size and have a spherical shape. Antibacterial and antibiofilm potential of synthesized silver nanoparticles against pathogenic organisms Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria were investigated. The in vitro cell scratch wounding assay is used to investigate the wound healing properties of synthesized nanoparticles. Pisonia Alba stabilized silver nanoparticles (PA@AgNPs), in comparison to Pisonia Alba (PA) extract, show effective wound healing characteristics by inducing the formation of collagen and serving as a capable wound healing agent.